Covalently bonded AMPS-based copolymerCSH hybrid as a fluid loss additive for oilwell saline cement slurry in UHT environment. (16th May 2023) - Zhang, Hang; Hu, Miaomiao; Li, Pengpeng; Liu, Ming; Yu, Yongjin; Xia, Xiujian; Liu, Huiting; Guo, Jintang
Highlights: The organic/inorganic hybrid fluid loss additive PANINI-C-S-H was synthesized and characterized. The PANINI-C-S-H hybrid exhibited more pronounced saturated saline cement slurry fluid loss control ability than PANI copolymer. The thermal decomposition temperature of PANINI-C-S-H hybrid was 61°C higher than PANI copolymer. With the dual synergy of adsorption behavior and plugging/filling effects, the PANINI-C-S-H hybrid could effectively optimize the cement grain distribution and increase the compactness of saturated saline cement filter cake. Abstract: The organic/inorganic hybrid fluid loss additive PANICSH was synthesized to adapt for high salinity cementing at ultrahigh temperatures (UHT, 200–240 °C). Unlike common physical blending, the PANI-C-SH was synthesized by grafting calcium silicate hydrate (CSH) from polycarboxylate copolymer PANI [P(AMPS-NNDMA-IA)] via "peptide coupling" and "sol–gel" reactions. When added into the UHT cement slurry, the hybrid PANICSH exhibited more pronounced saturated saline cement slurry fluid loss control ability (31 mL at 240 °C) than that of PANI copolymer (68 mL). The three-dimensional spatial morphology of PANICSH hybrid was able to plug and fill in the micro voids of the filter cake and resulted in effective refinements of the micro-pore structure, which compensated the deteriorated fluid loss control capacity caused by the weakened adsorption of copolymer PANI in saturated saline cement slurry.